Response of the low latitude mesosphere and lower thermosphere to the recent sudden stratospheric warming events of 2017–18 and 2019 - Sathishkumar, S.; Sridharan, S.; Krishnapriya, K.; Patil, P. T. (Frontiers in Astronomy and Space Sciences, 2024)
Upper mesospheric wind data acquired by the medium frequency radar at Kolhapur (16.7 o N, 74.2 o E) and MERRA-2 temperature and wind reanalysis datasets are used to investigate the dynamical response of the low-latitude middle atmosphere to the sudden stratospheric warming (SSW) events occurred during the 2017-18 and 2018-19 winters. When the amplitude of high latitude stratospheric planetary wave (PW) of zonal wavenumber 1 reduces considerably with the onset of the SSW, the low-latitude mesospheric PW over Kolhapur also shows considerable reduction in the PW activity. It is noteworthy 2 that the upper mesospheric winds are eastward for about three weeks after the onset of the SSW. The reduced PW activity is associated with the enhanced gravity wave activity in the meridional wind during the SSW 2018-19. The plane of propagation of gravity waves obtained from the perturbation ellipse method suggests that their predominant plane of propagation is in the north-south direction.The persistence of the eastward winds is suggested to be due to the interaction of the northward propagating gravity waves with the mean flow leading to the eastward acceleration due to Coriolis force.